2020
DOI: 10.1155/2020/8329310
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Procalcitonin Is Useful for Predicting the Severity of Acute Cholecystitis

Abstract: Background. Acute cholecystitis is a common complication of cholelithiasis. Delayed diagnosis may constitute morbidity and mortality; therefore, early diagnosis and determining the severity of acute cholecystitis are crucial. Objectives. This study aimed to determine the validity of blood procalcitonin (PCT) levels in assessing the severity of acute cholecystitis. Methods. The Emergency Department (ED) patients diagnosed as acute cholecystitis were included in the study. Patients were allocated into three seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Yuzbasioglu described a positive correlation between PCT and CRP and leukocyte levels. Sakalar et al also showed that PCT level was strongly correlated to acute cholecystitis severity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuzbasioglu described a positive correlation between PCT and CRP and leukocyte levels. Sakalar et al also showed that PCT level was strongly correlated to acute cholecystitis severity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also publications that examine plasma procalcitonin levels to determine the prognosis of acute cholecystitis. It was shown in the study of Sakalar et al[ 17 ] with 95 patients and in the study of Yuzbasioglu et al[ 18 ] with 200 patients, it was shown that procalcitonin levels determined the severity of acute cholecystitis effectively and significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Seven full texts were reviewed, of which four articles were eligible [25,33,34,39]. One additional article was identified from reviewing references of eligible articles [36] Therefore, the final analysis included five articles (four prospective cohort studies and one retrospective study).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thus, it was not included within the guidelines. Since then, there have been studies evaluating the role of PCT in diagnosis, severity stratification, and/or outcomes in AC [33,34]. It is timely that a comprehensive review of existing evidence is conducted to shed light if PCT could be included in AC management.…”
Section: Introductionmentioning
confidence: 99%